2020
DOI: 10.1177/1362361320942087
|View full text |Cite
|
Sign up to set email alerts
|

Increased emotional eating behaviors in children with autism: Sex differences and links with dietary variety

Abstract: Although food selectivity and so-called “picky” eating are well documented in autism spectrum disorder, emotion-linked eating has rarely been investigated. This study examined emotion-linked over- and under-eating based on parent ratings of these behaviors in 4- to 17-year-old children with autism spectrum disorder ( n = 190) as compared to same-age typically developing children ( n = 119). Children with autism spectrum disorder were rated as exhibiting both more emotional over-eating and more emotional under-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…Recent studies have corroborated this assumption: Wallace et al. (2021) found emotional eating to be increased in autistic girls along with van't Hof et al. (2020), who discovered that autistic traits at age six in girls of the general population were predictive of increased emotional eating at a later age, an association which was found to not be the case for boys from the general population.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Recent studies have corroborated this assumption: Wallace et al. (2021) found emotional eating to be increased in autistic girls along with van't Hof et al. (2020), who discovered that autistic traits at age six in girls of the general population were predictive of increased emotional eating at a later age, an association which was found to not be the case for boys from the general population.…”
Section: Discussionmentioning
confidence: 91%
“…They proposed that the girls' behavioural rigidity and restricted range of interests was more relevant in the development and maintenance of their disordered eating habits than difficulties in sensory processing. And even though restrictive and repetitive behaviours are thought to be more common in autistic men (Wilson et al., 2016), it could be that behaviours such as having preferences for a particular food brand (i.e., behavioural rigidity) or engaging in dieting behaviour (i.e., being busy with food/not eating as a specific and restricted interest) are yet another example of how ASD manifests itself differently in high functioning autistic girls and women than in autistic males (Rynkiewicz et al., 2016; Wallace et al., 2021). It is important to further investigate the roles of sensory sensitivities and restrictive and repetitive behaviours in the development and maintenance of these eating behaviours in autistic women in future research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sensory sensitivities, inflexibility and insistence on sameness, motor weaknesses) can affect activity and diet. In this special issue, Wallace and colleagues (2021) found that decreased consumption of vegetables and increased consumption of sweet foods (perhaps reflecting food selectivity due to ASD-related sensory sensitivities or rigidity) was linked to emotional over-eating in children with ASD, and was higher for autistic females than autistic males. This is one of several examples in this special issue highlighting unique findings for autistic women that cannot be ignored in the study of physical health in ASD.…”
Section: Theme 1: Eating and Physical Activity Concerns Are Not One-size-fits-all For People Who Have Autismmentioning
confidence: 95%